Bone biology - Dellavia, Claudia; Pellegrini, Gaia; Fiorin, Luiz Guilherme [UNESP] (Wiley, 2022)
Bone is a specialized mineralized connective tissue organized in lamellae that form a cortical or cancellous macrostructure. Although the bone has a rigid structure with an inert component, it is an extremely dynamic living complex, capable of responding to external stimuli by absorbing or dissipating impacts, healing when cracked or fractured, and growing. Physiologically, the bone undergoes the process of remodeling, suffering resorption and deposition in a harmonic way guided by cells. In clinical practice, this continuous anabolic and catabolic activity is used for regenerative treatments and dental implantation. Bone may interact with other materials that stimulate its healing and enter into the remodeling process. When non-resorbable materials are placed, usually titanium implants, the tissue establishes an intimate and functional contact with the implant (osseointegration) that is responsible for the success and later maintenance of the rehabilitation. In addition, bone may dissipate the occlusal forces and repair microcracks that occur in the early stages of fatigue as a result of damage accumulation, thus actuating a targeted remodeling. As part of the implant rehabilitation and management of bone substitutes, the healing of the wound in the soft tissues is an important facet of complete healing. Oral wounds heal faster than cutaneous wounds, passing through the same phases; mucosal healing usually occurs with minimal visible scars or hypertrophy, as myofibroblasts are the main type of cells that control the contraction of the matrix and the production of collagen.
Keywords: Angiogenesis; Epithelization; Granulation; Hemostasis; Inflammation; Proliferation; Remodeling; Scar; Tissue repair; Wound healing